Music of the twentieth century a study of its elements and structure - Leeuw, Ton de 1926-1996 (Amsterdam University Press, 2005)
Ton de Leeuw was a truly groundbreaking composer. As evidenced by his pioneering study of compositional methods that melded Eastern traditional music with Western musical theory, he had a profound understanding of the complex and often divisive history of twentieth-century music. Now his renowned chronicle Music of the Twentieth Century is offered here in a newly revised English-language edition. Music of the Twentieth Century goes beyond a historical survey with its lucid and impassioned discussion of the elements, structures, compositional principles, and terminologies of twentieth-century music. De Leeuw draws on his experience as a composer, teacher, and music scholar of non-European music traditions, including Indian, Indonesian, and Japanese music, to examine how musical innovations that developed during the twentieth century transformed musical theory, composition, and scholarly thought around the globe.
Title from publisher's bibliographic system (viewed on 15 Jan 2021)
Keywords: Geschichte 1900-1995; Geschichte 1900-2000; Music / 20th century / History and criticism; Twelve-tone system; Musik; Neue Musik